The Ethics of App‐Assisted Family Mediation. (31st May 2016) - Barsky, Allan E.
Abstract: This article explores ethical issues that mediators should consider when selecting and using digital programs (software/apps) as part of the mediation process. In particular, mediators should address ethical concerns related to duty of care, informed consent, privacy and confidentiality, boundaries, neutrality and fairness, and cross‐border mediation.